2019
DOI: 10.1038/s41366-019-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

Age at adiposity rebound in childhood is associated with PCOS diagnosis and obesity in adulthood—longitudinal analysis of BMI data from birth to age 46 in cases of PCOS

Abstract: Background:Adiposity rebound (AR), the second BMI rise in childhood at around the age of 6 years, is associated with obesity and metabolic alteration in later life. Given that polycystic ovary syndrome (PCOS) has a strong metabolic component, early life growth patterns could reveal a risk of PCOS. Thus, we aimed to investigate the associations between age at AR and PCOS diagnosis and BMI later in life.Materials and methods:This study is part of a prospective, population-based longitudinal study, where women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 30 publications
4
64
0
Order By: Relevance
“…The latter emulates the~60% diagnostic progression expected from a separate longitudinal study of PCOS families following newborn daughters into adulthood [18]. With regard to age at menarche, however, it is early [127], normal [128] or late [129] for women with PCOS, seemingly determined by weight during later childhood and at menarche. Overweight girls with PCOS are at greater risk for earlier age at menarche, while those who were thin before or at menarche are more likely to have a delayed menarchal age [130].…”
Section: Infant and Peripubertal Reproduction-related Endocrine And Omentioning
confidence: 71%
“…The latter emulates the~60% diagnostic progression expected from a separate longitudinal study of PCOS families following newborn daughters into adulthood [18]. With regard to age at menarche, however, it is early [127], normal [128] or late [129] for women with PCOS, seemingly determined by weight during later childhood and at menarche. Overweight girls with PCOS are at greater risk for earlier age at menarche, while those who were thin before or at menarche are more likely to have a delayed menarchal age [130].…”
Section: Infant and Peripubertal Reproduction-related Endocrine And Omentioning
confidence: 71%
“…Mismatches between prenatal and postnatal weights have led to the advance of the developmental origins of disease hypothesis [90]. The longitudinal prospective population-based study (Northern Finland Birth Cohort Study) found that women with PCOS had lower birth weights, experienced adiposity rebounds at younger ages, and had higher subsequent BMI values [91]. These findings are consistent with the concept that a mismatch between prenatal weight and postnatal weight gain is associated with increased risk for PCOS, ectopic fat storage, and hepatic steatosis [92–94].…”
Section: Pathophysiologymentioning
confidence: 99%
“…2 Furthermore, data from NFBC 1966 show association between early adiposity rebound during childhood and diagnosis of PCOS and obesity in adulthood. 85 However, PCOS is a complex condition, and it is likely that its relationship with obesity is also complex. It is important to consider possible mechanisms whereby PCOS may contribute towards further weight-gain or hamper successful attempts at weight-loss and maintenance of body weight through lifestyle means in women with this condition, outlined in this section.…”
Section: Polycystic Ovary Syndrome As a Risk Factor For The Developmementioning
confidence: 99%